Quality seaport : model building and empirical validation - Phang, Louise Foong Hung. (2010)
The purpose of this paper is to answer the research question of what forms a quality seaport by looking at the main attributes that contribute to it and thereby proposing and validating a model of a Quality Seaport. Our view of quality comes for three main areas, Quality Service, Quality Management Principles and Service Awards and Quality Models. Combining these factors, enablers and attributes that we have found from our literature review and interviews, we have come up with a survey and we will use the survey to validate these attributes. The survey was sent out to a total of 350 Freight Forwarders, Shipping Lines and Cargo Owners who are main users of the Singapore Port that we are focusing our study on for simplification purposes. A total of 37 usable questionnaires were returned and 6 interviews were conducted. The interviews were done with representatives from the 3 main stakeholder groups, the regulatory authority – Maritime Port Authority of Singapore (MPA), the customers of the port – Glory Ship Management, Mediterranean Shipping Company (MSC) and American-Pacific Lines (APL), and the port’s terminal operators – Jurong Port (JP) and Port of Singapore Authority (PSA). The results found 14 attributes that respondents found significant and important and these attributes will form our model. An additional 2 more factors have been added in and will be discussed in further sections.